Phase I single center trial of ketogenic diet for adults with traumatic brain injury. (February 2022) - Arora, Niraj; Litofsky, N. Scott; Golzy, Mojgan; Aneja, Rachna; Staudenmyer, Danielle; Qualls, Kathyrn; Patil, Sachin
Summary: Background: Traumatic Brain injury (TBI) is a major cause of mortality and morbidity in the United States. Ketogenic diet (KD) has been shown to have neuroprotective effects in acute brain injury, but limited data about its use in adult TBI patients is available. The objective of this study is to investigate the feasibility and safety of ketogenic diet (KD) for adult TBI patients in the Neuroscience Intensive Care Unit (NSICU). Methods: TBI patients admitted to NSICU between June 2019 to March 2021 were enrolled in this single-center, open label, single-arm prospective intervention study. The primary feasibility outcome was achievement of ketosis (detection and maintenance of serum beta-hydroxybutyrate (BOB) levels above normal); secondary outcomes included laboratory and clinical adverse effects related to KD. Results: 10 adults with TBI with Abbreviated Injury Score (AIS)-Head ≥3 and ventriculostomy catheter to monitor intracranial pressure met inclusion/exclusion criteria and were placed on KD. Mean age was 47 years, and all patients were male. Eight out of 10 patients achieved ketosis within mean 2.2 days. KD was initiated within 8–33 h (average 23 h) of hospital admission. No clinical adverse effects were noted, 2 patients developed hypertriglyceridemia and 1 patient developed hypoglycemia. Serum glucose showed a decreasing trend in most patients. Conclusions: This pilot study shows that KD is feasible in the management of TBI patients. A randomized controlled trial (RCT) is justified to further understand the optimal serum BOB levels, dose and duration of KD in TBI and its effect on the outcome. ClinicalTrials.gov Identifier: NCT03982602, Registered 06/11/2019, https://clinicaltrials.gov/ct2/show/NCT03982602?term=brain+injury&cond=ketogenic+diet&draw=2&rank=3 .